5 - Cultural and Resource Determinants of Severe Maternai Morbidity: Lessons /rom Some 'Near Miss' Experiences - Grace Bantebya-Kyomuhendo, (African Sociological Review, 2004)
In Uganda severe maternai morbidity remains a problem to reckon with. This paper reports part of a wider study conducted in Kiboga, Hoima and Kampala districts, Uganda between 1999 and 2000 (Okong et al. 2001), the aim of which was to document the circumstances that led women to death-threatening medical crisis situations. It emerged that severe maternai illness is not necessarily a result of direct (biomedical) causes per se but may stem from other factors deeply rooted in culture and gender relationships. These factors notwithstanding, women are hampered by deficiencies in the.formai health care system lncluding inter alia inexperienced health workers, especially at lower level units, poor referral systems and the lack qfà well1'unctioning transport system, limited space in the wards or operating theatre, and inability to access the busy health staff: These constraints often lead to critical delays, which aggravate women 's morbidity experiences. Appropriate interventions, including delivery of culturally accepted maternai health information and addressing the lack of quality maternai health services, are required.